Comparing open reduction and internal fixation versus closed reduction using dual-point distraction and percutaneous fixation for treating calcaneal fractures - Batıbay, Sefa Giray (Jt Dis Relat Surg, 2020)
OBJECTIVES: This study aims to compare the early clinical, functional and radiographic outcomes of a small cohort of patients with calcaneal fractures treated with closed reduction using a dual- point distraction system and the traditional lateral approach. PATIENTS AND METHODS: We prospectively treated 40 patients with calcaneus fractures who presented to our emergency department between January 2017 and February 2018. In total, 35 patients (22 males, 13 females; median age 39.8 years; range, 19 to 57 years) were included in this study since five patients were not followed up. Fractures were classified according to the Sanders classification system using computer tomography images. Clinical outcomes including postoperative two-week visual analog scale (VAS) score, sickness absence period, operating time and complication rate were recorded. RESULTS: The mean follow-up period was 24 months. Closed reduction using dual-point distraction and percutaneous fixation (group 1) was performed in 17 patients, whereas the extended lateral approach (group 2) was used in 18 patients. There were no significant differences between both groups in age, follow- up outcomes and Sanders classification. Operating time was significantly shorter in group 1 than in group 2. At postoperative two weeks, VAS scores were significantly lower in group 1 than in group 2. The complication rate and sickness absence period were significantly lower in group 1 than in group 2. CONCLUSION: Closed reduction using dual-point distraction can be preferred owing to many advantages including considerably decreased risk of wound complications, sickness absence period and length of hospital stay as well as superior postoperative rehabilitation with a low pain score.